Within- and between-individual associations between sleep and cognition in older community-dwelling individuals - della Monica, Ciro; Ravindran, Kiran K. G.; Atzori, Giuseppe; Trender, William; Hampshire, Adam; Skene, Simon S.; Hassanin, Hana; Revell, Victoria; Dijk, Derk-Jan (Frontiers in Aging, 2026)
IntroductionCross-sectional and interventional studies have demonstrated that sleep has a significant impact on waking brain function, including alertness and cognitive performance. Few studies have assessed whether spontaneous night-to-night variation in sleep is associated with variation in brain function within an individual. How this compares to inter-individual variation in sleep and cognition and their associations also remains largely unknown. These questions are of particular interest in the context of aging because both sleep and cognitive abilities are altered.MethodsFurthermore, older people have been reported to be less sensitive to sleep loss. Here, we investigated the relationship between sleep and cognition by quantifying associations between intra-individual variation in sleep and cognition, along with associations between inter-individual variation in sleep and cognition, in 35 cognitively intact older adults (70.8 ± 4.9 years; mean ± SD; 14 female individuals) living in the community. Subjective and actigraphic sleep measures and daily digital assessments of cognition (9 cognitive tests; 19 variables) were obtained over a 2-week period. The cognitive test battery probed a wide range of cognitive functions, including reaction time, working memory, attention, and problem-solving. Principal component analysis (PCA) identified four principal sleep components, namely, sleep duration, sleep efficiency, subjective sleep quality, and nap effect. Mixed model analyses were conducted with mean and deviation-from-the-mean cognitive variables to quantify how inter- and intra-individual variations in sleep were associated with inter- and intra-individual variations in cognition.ResultsLonger sleep duration was associated with faster reaction times in both the inter- and intra-individual analyses and with reduced errors in the inter-individual analyses. Higher sleep efficiency was associated with faster reaction times in both the intra- and inter-individual analyses. In contrast, aspects of cognition relating to learning, visual memory, verbal reasoning, and verbal fluency were not associated with sleep.DiscussionThese data show that, in older people, some aspects of waking function are sensitive to night-to-night variation in sleep duration and efficiency, implying that interventions targeting these aspects of sleep may be beneficial for waking function in aging.